TLK2 promotes the proliferation, migration and invasion of human breast cancer cell lines - XIONG Yu-yuan, CHEN De-jie, MENG Lin, YAN Shan (Jichu yixue yu linchuang, 2021)
Objective To explore the effects of TLK2 in breast cancer (BC) cells and its possible mechanism. Methods Immunohistochemistry and Western blot were used to detect the expression of TLK2 in BC tissues and cell lines. RT-qPCR was employed to detect the expression of TLK2 mRNA and miR-622 in BC tissues and cell lines. CCK-8, BrdU and Transwell assays were used to detect the effects of TLK2 over-expression plasmid and miR-622 inhibitors on the proliferation, migration and invasion of HCC70 cells. The targeted regulatory relationship between miR-622 and TLK2 was predicted and verified by Target scanning online analysis database and dual-luciferase reporter gene, respectively. Results The expression of TLK2 in BC tissues or cell lines was significantly up-regulated (P＜0.05), and TLK2 significantly promoted the proliferation, migration and invasion of HCC70 cells (P＜0.01). The possible mechanism suggested that miR-622 can bind to the 3′UTR of TLK2. Conclusions TLK2 is involved in promoting the proliferation, migration and invasion of BC cells, and is negatively regulated by miR-622.